Peran Orang Tua dalam Mengatasi Gangguan Kecemasan Siswa SD terkait Pembelajaran Matematika - Choiriyah, Umatul; Mu’arifah, Maulida Putri; Nurfaizah, Desta Ariani; Pawestri, Syarifah Anjani; Nurohmah, Lutfiana; Sukardi, Rendi Restiana; Yuniarti, Yeni (Teaching, Learning, and Development, 2023)
Abstract: This research aims to find out how important the role of parents is in elementary school students' anxiety regarding learning mathematics. The research method we use is a qualitative research method with a case study approach. Researchers used interview instruments, questionnaires, questionnaires and documentation in the data collection process. The research results showed that of the 31 respondents, all had anxiety related to learning mathematics, although at different levels, namely mild, moderate and severe. Most of them feel anxious when working on questions and approaching mathematics exams. The role of parents in dealing with children's anxiety is still not optimal. In overcoming anxiety in children, parents only tend to provide assistance, motivation and enthusiasm to continue learning. So, parents still don't understand how to provide strategies for dealing with anxiety that occurs in children. Abstrak: Penelitian ini bertujuan untuk mengetahui seberapa penting peran orang tua terhadap kecemasan siswa SD terkait pembelajaran matematika. Metode penelitian yang kami gunakan ialah metode penelitian kualitatif dengan pendekatan studi kasus. Peneliti menggunakan instrumen wawancara, angket, kuisioner dan dokumentasi dalam proses pengambilan data. Hasil penelitian menunjukkan bahwa dari 31 responden, semua memiliki kecemasan terkait pembelajaran matematika walaupun dengan tingkatan yang berbeda-beda yaitu ringan, sedang, dan berat. Sebagian besar dari mereka merasa cemas ketika mengerjakan soal dan menjelang ujian matematika. Peran orang tua dalam mengatasi kecemasan anak masih belum maksimal. Dalam mengatasi kecemasan pada anak, orang tua hanya cenderung memberikan pendampingan, motivasi, dan semangat untuk terus belajar. Sehingga, orang tua masih belum paham dalam memberikan strategi untuk mengatasi kecemasan yang terjadi pada anak.